Dukungan Petugas Terhadap Perilaku Konseling Dan Tes HIV (Human Immunodeficiency Virus) Ibu Hamil Di Kelurahan Kepanjenlor Kecamatan Kepanjenkidul Kota Blitar - Dwi Ertiana (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2020)
regnant women who received HIV Counseling and Testing (KTHIV) services in the work area of ​​UPTD Puskesmas Kepanjenkidul District in Blitar City in 2018 amounted to 65.12% and the least achievement was Kepanjenlor sub-district which was 37.23%. This study aims to determine the relationship of officer support for HIV pregnant women counseling and testing behavior in Kepanjenlor Village, Kepanjenkidul District, Blitar City. This is a correlation study with a case control survey, using a retrospective approach. The population of pregnant women is 75 with 43 samples taken using simple random sampling technique. Research dated June 17-29, 2019, instruments used questionnaires and medical records, using the Spearman rank statistical test. The results of the study obtained officers support for HIV counseling and testing of pregnant women as many as 31 respondents (72.1%) in the good category, counseling behavior and 29 pregnant women HIV tests (67.4%) were in the good category, and based on statistical tests it was found that p value = 0.002 α <0, 05 and coefficient correlation 0.453 showed there was a relationship between the officers' support for counseling behavior and HIV testing of pregnant women in the Kelurahan Kepanjenlor Kepanjenkidul District, Blitar City. Staff support is needed both emotional support, assessment / appreciation support, information support and instrumental support so that pregnant women have the awareness and willingness to do HIV counseling and testing to find out their HIV status.